Weaving Indigenous Knowledges into the Classroom as a Tool to Combat Racism - Danyluk, Patricia; Burns, Amy; Poitras Pratt, Yvonne; Wessel, Samara; James Thomas, Saria; Trout, Lisa; Lorenz, Danielle; Kendrick, Astrid; Kapoyannis, Theodora; Crawford, Kathryn L.; Lemaire, Eva; Hill, Joshua; et al. (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2024)
Two years after the introduction of the new Teaching Quality Standard in Alberta, Indigenous and non-Indigenous researchers from eight teacher education programs came together to examine how teachers were weaving Indigenous knowledges into their classrooms. The fifth competency of the standard requires that all Alberta teachers possess a foundational knowledge of First Nations, Métis, and Inuit and apply that knowledge in the classroom. Two hundred and forty-seven teachers, both non-Indigenous and Indigenous, responded to a survey, and another 30 participated in follow-up interviews. Results point to challenges and successes that teachers have experienced, the people that support their work, and how the integration of Indigenous knowledges acts as a tool to combat racism against Indigenous Peoples. Although teachers reported increased efficacy in applying a foundational knowledge of Indigenous Peoples, a multicultural perspective prevented some from understanding the unique nature of racism against Indigenous Peoples.